RANCANGAN DAN KONTRUKSI WATER-JACKET COOLER PADA ALAT EKSPERIMEN USSA-FTS01 - Pitanova, Thasyah; Juarsa, Mulya; Yuliaji, Dwi (UNIVERSITAS IBN KHALDUN BOGOR, 2022)
ABSTRAK Water Jacket Cooler merupakan komponen dari alat uji untai simulasi sirkulasi alam. Memiliki fungsi sebagai penyerap panas pada pipa untai. Desain dan rancang bangun water jacket cooler telah dilakukan dengan menggunakan prinsip tabung bejana tekan. Spesifikasi material menggunakan mild steel ASTM A36, volume bejana 4 liter, jumlah aliran 3 phase. Pengujian dilakukan dengan memberikan udara bertekanan ke dalam tabung WJC USSA-FTS01 dengan variasi 0,5 bar sampai dengan 5 bar kemudian hasilnya dicatat. Tegangan aktual material , tegangan longitudinal , tegangan tangensial , tegangan longitudinal akibat tekanan hidrostatik , tegangan tangensial akibat tekanan hidrostatik . Hasil analisa sambungan baut, tegangan tarik material baut , tegangan tarik aktual baut . Hasil analisa sambungan las, tegangan tarik kawat las E6013 , tegangan aktual logam las . Hasil analisa struktur bejana tekan, sambungan baut dan pengelasan telah memenuhi persyaratan, yaitu tegangan-tegangan yang terjadi tidak melebihi tegangan ijin material. Kata kunci : Bejana tekan; Sirkulasi alam; tegangan material; untai simulasi; water jacket cooler ABSTRACT Water Jacket Cooler is a component of the natural circulation simulation strand test equipment. Has a function as a heat absorber on the strand pipe. The design and design of the water jacket cooler has been carried out using the principle of the pressure vessel tube. Material specifications using ASTM A36 mild steel, 4 liter vessel volume, 3 phase flow rate. The test is carried out by applying compressed air into the USSA-FTS01 WJC tube with a variation of 0.5 bar to 5 bar then the results are recorded. Actual stress of material 6.5 í— 105 Nâ„m2, longitudinal voltage 8.7 í— 105 Nâ„m2, tangential voltage 1.7 í— 105 Nâ„m2, longitudinal stress due to hydrostatic pressure 1.1 í— 106 Nâ„m2, tangential stress due to hydrostatic pressure 2.2 í— 106 Nâ„m2. The results of the bolt connection analysis, the tensile stress of the bolt material 8 í— 108 Nâ„m2, the actual tensile stress of the bolt 8.4 í— 107 Nâ„m2. The results of the welding connection analysis, the tensile stress of the welding wire E6013 414 í— 106 Nâ„m2, the actual stress of the weld metal 5,3 í— 103 Nâ„m2. The results of the analysis of the structure of the pressure vessel, bolt connection and welding have met the requirements, namely the stresses that occur do not exceed the material permit stress. Keywords : Natural circulation; Material; Pressure vessels; Stress; Strand simulation; water jacket cooler